Peran nilai pancasila: pembentukan karakter sosial mahasiswa - Faliha, Bariza Fithri Ummi (Maliki Interdisciplinary Journal, 2025)
Pancasila values still hold an important role in shaping the social character of university students amid rapid changes in today’s era. Many students face challenges such as the influence of social media, individualistic attitudes, and an instant lifestyle, which gradually weaken social attitudes based on care and togetherness. This paper describes how the values of divinity, humanity, unity, deliberation, and justice are practiced by students in their daily campus life. These values remain a useful guide that helps students behave with greater empathy, respect, and fairness. Therefore, support from the campus environment is essential to strengthen the application of these values through activities that promote togetherness, cooperation, and good example from educators. In this way, strengthening Pancasila values not only benefits the personal development of students but also equips them to actively contribute to building a democratic, ethical, and civilized nation.